2008
DOI: 10.1890/07-0153.1
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Evaluation of the Insurance Hypothesis in Diversity–stability Models

Abstract: An important stabilizing mechanism in most diversity stability models is the insurance hypothesis, which involves correlation/covariance relationships among species. These models require that species do not fluctuate synchronously over time: that is, the correlation between pairs of species does not equal 1.0. However, the strength of this stabilizing mechanism increases as correlations decline away from 1.0, especially as they become more negative and also as the summed covariance across all species pairs bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 71 publications
4
53
1
Order By: Relevance
“…Using yearly variation in total detections and mean detections as proxies for abundance, we found scaling parameters above one In contrast, we found that assemblages with higher species richness did not exhibit more negative covariance (frugivores: β < 0.01, R 2 < 0.01, P = 0.90; granivores: β < 0.01, R 2 < 0.01, P = 0.78; insectivores: β < 0.01, R 2 < 0.01, P = 0.63; nectarivores: β = 0.06, R 2 = 0.07, P = 0.10). In fact, we found no evidence that populations exhibit negative covariance in population size over time (17)(18)(19)29), although positive correlations were sometimes present (Fig. 3).…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Using yearly variation in total detections and mean detections as proxies for abundance, we found scaling parameters above one In contrast, we found that assemblages with higher species richness did not exhibit more negative covariance (frugivores: β < 0.01, R 2 < 0.01, P = 0.90; granivores: β < 0.01, R 2 < 0.01, P = 0.78; insectivores: β < 0.01, R 2 < 0.01, P = 0.63; nectarivores: β = 0.06, R 2 = 0.07, P = 0.10). In fact, we found no evidence that populations exhibit negative covariance in population size over time (17)(18)(19)29), although positive correlations were sometimes present (Fig. 3).…”
Section: Resultsmentioning
confidence: 64%
“…It may confer resilience, because if species react differently to disturbances, then there is a higher likelihood that guild abundance will remain constant after ecosystems change (7,17). Second, negative covariation in abundance between species in the same guild can confer resilience by causing the total abundance of a guild to remain constant through disturbances (17)(18)(19). For example, the decline of one insect-eating bird after a disturbance could be offset by an increase in abundance of another species within the same guild.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous synthesis studies that have calculated the variance ratio at multiple sites for several taxa reported more positive than negative covariance (Houlahan et al 2007, Valone andBarber 2008). These patterns contrast with experimental findings, which often provide evidence of compensatory dynamics (Klug et al 2000, Hector et al 2010.…”
Section: Discussionmentioning
confidence: 82%
“…by the insurance model (Yachi & Loreau 1999), which bases diversity effects on the fact that diverse communities are more likely to show compensatory dynamics than communities of low biodiversity. Although compensatory dynamics in response to environmental fluctuation has been analysed in natural systems (Vasseur & Gaedke 2007, Winfree & Kremen 2009) and experiments (Gonzalez & De s campsJulien 2004, Downing 2008, there is considerable debate as to whether compensatory dynamics generally prevail in ecosystems (Houlahan et al 2007, Valone & Barber 2008.…”
Section: Abstract: Stability · Species Richness · Species Identity ·mentioning
confidence: 99%